Role of the IL-23/IL-17 Pathway in Rheumatic Diseases: An Overview - Schinocca, Claudia; Rizzo, Chiara; Fasano, Serena; Grasso, Giulia; La Barbera, Lidia; Ciccia, Francesco; Guggino, Giuliana (Frontiers in Immunology, 2021)
Interleukin-23 (IL-23) is a pro-inflammatory cytokine composed of two subunits, IL-23A (p19) and IL-12/23B (p40), the latter shared with Interleukin-12 (IL-12). IL-23 is mainly produced by macrophages and dendritic cells, in response to exogenous or endogenous signals, and drives the differentiation and activation of T helper 17 (Th17) cells with subsequent production of IL-17A, IL-17F, IL-6, IL-22, and tumor necrosis factor α (TNF-α). Although IL-23 plays a pivotal role in the protective immune response to bacterial and fungal infections, its dysregulation has been shown to exacerbate chronic immune-mediated inflammation. Well-established experimental data support the concept that IL-23/IL-17 axis activation contributes to the development of several inflammatory diseases, such as PsA, Psoriasis, Psoriatic Arthritis; AS, Ankylosing Spondylitis; IBD, Inflammatory Bowel Disease; RA, Rheumatoid Arthritis; SS, Sjogren Syndrome; MS, Multiple Sclerosis. As a result, emerging clinical studies have focused on the blockade of this pathogenic axis as a promising therapeutic target in several autoimmune disorders; nevertheless, a greater understanding of its contribution still requires further investigation. This review aims to elucidate the most recent studies and literature data on the pathogenetic role of IL-23 and Th17 cells in inflammatory rheumatic diseases.